Chloride transport in the reinforced concrete column under the marine environment: Distinguish the atmospheric, tidal-splash and submerged zones. (May 2022) - Liu, Qingchen; Sun, Lianfang; Zhu, Xingji; Xu, Longjun; Zhao, Guochen
Abstract: Under the marine environment, the penetration of chloride ions in reinforced concrete (RC) structures has been widely studied by coupling with moisture and carbonation. However, most of the previous studies only focus on a single environmental region (e.g., atmospheric, tidal-splash, submerged zone), ignoring the influence of their integrity. Here, a comprehensive finite element (FE) model is proposed to observe the chloride distribution along the elevation of RC columns. Various parametric studies are conducted to investigate their effect on chloride profiles. At different regions, the evolutions of chloride non-uniform distribution versus exposure time are also analyzed. As consequences, relative to the atmospheric zone, chloride profiles in the tidal-splash and submerged zone are more sensitive to rebar size and concrete cover. The non-uniformity of chloride profiles in the tidal splash zone is more apparent around the middle rebar than around the corner rebar. Due to the long-term carbon dioxide pollution, carbonation eventually extends to the submerged zone, which causes the increase of chloride concentration along with the depth of rebar. This study extends the investigation of chloride distribution along the elevation direction of an RC column, towards a more comprehensive prediction of chloride-induced corrosion failure.